Site-selectively generated photon emitters in monolayer MoS2 via local helium ion irradiation - J. Klein (Nature Portfolio, 2019)
Light emitters can be induced in transition metal dichalcogenides by defect engineering, but challenges remain in their controlled spatial positioning. Here, the authors irradiate monolayer MoS2 with a sub-nm focused helium ion beam to deterministically create defects, and obtain spectrally narrow emission lines that produce photons in the visible spectral range